Community preparedness towards flood calamity from the perspective of local leaders / Nurul Aliya Azmi - Azmi, Nurul Aliya (2015)
Flooding is the most significant natural hazard in Malaysia. In recent years, flash floods have caused havoc in the country but the precautionary measures in disaster preparedness are still lacking. Therefore, the purpose of this research project is to focus on the community as the key actor or primary beneficiary of disaster preparedness. A qualitative approach was undertaken to evaluate community preparedness towards flood calamities in flood-prone areas in West Malaysia. Respondents from nine different regions shared their insights and experiences on the communities’ preparations in anticipation of the annual flood season. The findings showed that communities were not prepared for the flooding although they were informed of the pending disaster. The preparation by government agencies were not enough to match with the large size communities and villages inundated with flood. The community leaders acknowledged that having emergency drills and sharing information may enhance awareness before the flooding but not during the disaster period. The implication of this study is that disaster preparedness should be part of the standard operating procedure for communities that are prone to flooding. Educating and training the communities on disaster preparedness is suggested in order to minimize casualties.